Inequality - worldwide trends and current debates - Stephan Klasen; Nathalie Scholl; Rahul Lahoti; Sophie Ochmann; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
Income inequality has been rising in many developing countries since the 1980s. At the same time, global income inequality has been roughly stable (or even falling slightly) and there is great heterogeneity in within-country inequality trends across countries and regions. Non-income inequality tends to have fallen, both within and between countries. There is no empirical evidence that rising inequality is an inevitable consequence of economic growth; similarly, the evidence of the impact of changes in inequality on growth is also inconclusive, although higher levels of inequality appear to be harmful for subsequent development. At the same time, reducing inequality is seen as important to promote greater fairness as well as to speed up poverty reduction. To study trends in inequality, we use a framework where income inequality is related to inequality in assets (land, labor, human capital, and physical capital), return to these assets, inequality in private transfers, and redistribution by the state. Trends in inequality are tied to these different drivers which differ greatly by country and over time. This framework also generates opportunities for policy intervention to tackle inequality. This will, however, depend greatly on the country. As a result, it is useful to start a policy framework with an inequality diagnostics to identify the most important drivers of levels and changes in inequality in a particular country; this is also an activity where bilateral development partners can play an important supporting role. When it comes to particular policy issues, some of the issues that have been discussed for a long time remain highly relevant, including land reform (where land is still an important asset), pro-poor educational policies, rural infrastructure, and a focus on improving agricultural productivity of poor farmers. At the same time, increasing the redistributive role of the state through a higher tax take (to be achieved via broadening the tax base, increasing tax compliance, increase resource taxes), and increasing pro-poor social transfers. On the international dimension, there is now a greater emphasis on assisting developing countries with fighting tax evasion and tax avoidance of firms and individuals. As a single bilateral donor, it is not easy to have a significant impact on inequality and an explicit aid program on inequality reduction might also be politically contentious. In principle, the potential is there for significantly affecting inequality via technical cooperation assisting states (and potentially non-state actors) in implementing an inequality-reducing agenda. Budget support and other systemic approaches can of course also support an overall agenda of reducing inequality, as can investment projects if they focus on the policy-areas for inequality reduction outlined here.
Keywords: 330